More than learning English? The impact of university intensive English language program attendance on international student academic achievement - Clark, Adam T.; Lippincott, Dianna; Kim, Jeongeun (Education Policy Analysis Archives, 2021)
This study frames intensive English language programs (IEPs) in institutions of higher education as potential vehicles for social justice among marginalized international students. In this study we examine the differences in academic achievement between international students who enter a university through an English proficiency test and those who pass through an IEP. We compared both populations through nearly 900 cases, out of a sample of 4888, who had similar language proficiency at the time of enrolling at a large research-intensive university in the Southwest of the United States. The results revealed great similarity between the populations of students indicating that as an intervention-style program, the IEP was successful in meeting the linguistic and academic needs of the students. The study also revealed potential implications for higher education policy in ensuring both program quality and benefit to students. The paper also raises issues of equity in terms of the lack of analysis in long-term outcomes for these types of programs compared to other interventions, the need for expansion of international student data collection by institutions of higher education and overall transparency in pre-university programs.